Detection of exosomal MicroRNAs in milk of different animal species and investigation of their Temperature–Dependent changes - Celık, Ahmet; Vural, Aydın; Yıldırım, Ibrahim Halil (Revista Científica de la Facultad de Ciencias Veterinarias, 2025)
This study aimed to investigate the presence of specific microRNAs (miRNAs; miRNA–15a, miRNA–34a, miRNA–223, and miRNA–29b) in the milk of cows, buffalo, sheep, goats, and donkeys which are associated with cancer, immune system, and osteoblast development in humans. Additionally, the effect of heat treatment on these miRNAs was investigated. Milks were heat treated at 63°C for 30 min (P1), 90°C for 10 min (P2), and 135°C for 1–3 seconds. The presence of miRNA–15a, miRNA–34a, miRNA–223, and miRNA–29b were detected in the milk of cows, buffalo, sheep, goats, and donkeys. It was observed that these miRNAs responded differently to heat.